Lo soldadesco en la poesía de Héctor Viel Temperley: amor, ideales y masculinidad factibles - Arancet Ruda, María Amelia (Pontificia Universidad Católica del Perú, 2023)
According to critics, Viel Temperley is an Argentine mystical poet, but here we address a different facet, operative in relation to subjective representation and the encoding of a worldview: the iteration of military figurations, especially those of the soldier and its variants, in texts, paratexts and epitexts the latter, crucial in this work to validate the explored inclination, also supported by extraliterary documents. There is a multivocal repertoire of soldiery themes, deeply rooted in Argentine history and, furthermore, associated with the masculine imaginary of a particular era. This repertoire constructs the masculine self, but according to a subverted and destabilizing version, which ranges from love to heroism, even to the freedom of poetry. Due to this anti-system dissent, the figure of Juan Lavalle, dear to our author, is a kind of double in several compositions, and it sheds light on some of the meanings that soldiery acquires in Viel’s work.

Desde la crítica, Viel Temperley es un poeta místico argentino, pero aquí abordamos otra faceta, operativa en relación con la representación subjetiva y con el cifrado de una cosmovisión: la iteración de las figuraciones milicianas, especialmente del soldado, con sus variantes, en textos, paratextos y epitextos estos últimos, cruciales en este trabajo para fundamentar la inclinación indagada también en documentos extraliterarios. Hay un repertorio soldadesco, multívoco, arraigado en la historia argentina y, además, asociado con el imaginario masculino de una época. Este repertorio construye al yo varonil, pero según una versión subvertida y desestabilizadora, que va desde el amor al heroísmo hasta la libertad de la poesía. Por esta disidencia antisistema, la figura de Juan Lavalle, dilecta para nuestro autor, es una suerte de doble en varias composiciones e ilumina algunas de las significaciones que lo soldadesco adquiere en Viel.
Soldiery in the Poetry of Viel Temperley: Love, Ideals and Feasible Masculinity
Keywords: Soldiery; War history; Masculinity; Love; Soldadesca; Historia bélica; Masculinidad; Amor; https://purl.org/pe-repo/ocde/ford#6.02.06